Línea de accesorios inspirada en la faja del pueblo Natabuela - Maldonado Montalvo, Cinthya Maribel (2020)
The fundamental purpose of the project is the creation of a line of accessories that integrates within its configuration the sash used in the traditional clothing of the Natabuela (Chumbi) community\; its cultural value, the transmission of artisan techniques (backstrap loom) to the new generations and the recognition of the unique and invaluable work of artisans\; fully justify the motivation for conducting this research. After specifying the problem and raising the necessary justifications, with the consolidation of the state of the art, the theoretical and conceptual bases are established that support the knowledge of the customs of the Natabuela people and the techniques of the construction of girdles. Subsequently, a fieldwork is developed aimed at obtaining data on consumer profiles and consumption trends, which make possible product alternatives that can be applied as the basis of the project proposal, applying a diagnostic investigation. Finally, on the theoretical bases and the results, an innovative proposal is consolidated that integrates artisanal techniques for the elaboration of a line of accessories, with identity elements of the culture. The project developed is of a causal descriptive type with an approach oriented to the application of mixed research methodologies. Through interviews with five older adults representing the community and thirty surveys applied to the group of women belonging to the Kichwarimakuk Natabuelapi collective. After collecting and organizing the information, the results were interpreted and discussed to arrive at the proposal, which is supported by the Double Diamond design methodology, as well as processes related to the creation of collections. such as: creative process, illustration, study of materials, technical sheets, pattern making and prototyping. Once the proposal was consolidated, it was successfully socialized and validated by the Natabuela community and the target audience, allowing its commercial and productive acceptance to be measured\; The data reveals that the acceptance of the accessories line is 90% and that the community is interested in strengthening fair trade and supporting the work of the artisan.